--if you lived 100 years ago - McGovern, Ann.; DiVito, Anna. (New York : Scholastic, 1999)
Describes what life was like in New York City, then the largest city in the United States, during the 1890's.
G5
Keywords: New York (N.Y.) -- History -- 1865-1898 -- Juvenile literature; New York (N.Y.) -- History -- 1898-1951 -- Juvenile literature; New York (N.Y.) -- Social life and customs -- 19th century -- Juvenile literature; United States -- History -- 1865-1921 -- Juvenile literature; United States -- Social life and customs -- 1865-1918 -- Juvenile literature; New York (N.Y.) -- History -- 19th century; New York (N.Y.) -- Social life and customs -- 19th century; United States -- History -- 19th century; United States -- Social life and customs -- 19th century